FABRIKASI DAN KARAKTERISASI NANOGENERATOR BERBASIS NANOFIBER-NANOWIRE ZnO - Sholahuddin, Imam; Hentihu, M. Fahrur Rozy (ROTOR, 2015)
Fiber diffusion process when the fiber is still green on a plate collector and the thermal decomposition process followed by the formation of ZnO crystal nucleation has a very large role of the morphology of the final form of fiber products. Conversely, a positive result occurs in nanowire growth process. At the time of natural air pressure conditions and the presence of oxygen in the air in the process of sintering for 2 hours without using a catalyst, ZnO crystals can grow by itself (self-growth) into a nanowire. As a material nanogenerator, this situation provides an additional active area to excite the tap-off force into electrical voltage of up to 234.55 mV (2 Î¼â / min).